FORMATION OF KEY COMPETENCIES IN HISTORY LESSONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article examines the issues of competence, the importance of key competencies, the study and systematization of methods, methods and means of forming general competencies in the process of teaching history.